Preoperative inflammatory markers predict postoperative clinical outcomes in patients undergoing heart valve surgery: A large-sample retrospective study - Tian, Hongni; Jiang, Xuetao; Duan, Guangyou; Chen, Jie; Liu, Qi; Zhang, Yamei; Li, Shiqi; Bao, Xiaohang; Huang, He (Frontiers in Immunology, 2023)
Introduction Preoperative inflammation affects the postoperative outcomes of patients undergoing heart valve surgery. This study aimed to explore the role and predictive effects of preoperative inflammation on the primary outcomes after valvular cardiac surgery. Methods This retrospective study utilized a medical recording system to screen 5075 patients who underwent heart valve surgery. Data on the C-reactive protein (CRP) levels, erythrocyte sedimentation rate (ESR), and neutrophil-to-lymphocyte ratio (NLR) before heart valve surgery were collected from the hospital’s medical system. Postoperative hepatic insufficiency, acute kidney injury, heart failure, and myocardial damage were assessed using blood indicators. Patients with and without prolonged mechanical ventilation, extended intensive care unit stays, prolonged hospital stays, and death within 30 days after surgery (considered the primary outcome in this study) were compared. Group comparisons, receiver operating characteristic (ROC) curve analyses, and logistic analyses were performed to determine the associations between preoperative inflammation and outcomes after heart valve surgery. Results A total of 3249 patients were included in the analysis. Significant differences in CRP level, ESR, and NLR were found between patients with and without postoperative adverse outcomes. ROC analysis showed that CRP levels >5 mg/L effectively predicted postoperative heart failure, and NLR >3.5 had a good predictive effect on all-cause mortality within 30 days after surgery. Patients with CRP levels >5 mg/L had a higher incidence of postoperative heart failure than other patients (20.7% vs. 12.6%, P<0.001), with a relative risk of 1.447 (95% confidence interval: 1.155–1.814). Patients with NLR >3.5 had a higher incidence of death within 30 days after surgery (5.3% vs. 1.2%, P<0.001), with a relative risk of 3.236 (95% confidence interval: 1.773–5.906). Conclusion Preoperative inflammation can affect postoperative outcomes in patients undergoing heart valve surgery. CRP level >5 mg/L and NLR >3.5 can effectively predict postoperative heart failure and death within 30 days after surgery, respectively.